2023
DOI: 10.1007/s00432-023-04720-3
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with Fluoropyrimidine and cetuximab or bevacizumab after first line FOLFOX-chemotherapy in metastatic colorectal cancer according to RAS or BRAFV600E mutation status

Abstract: Fluoropyrimidine (FP) and oxaliplatin-based chemotherapy is the standard rst-line treatment for metastatic colorectal cancer (mCRC); however, oxaliplatin-induced neuropathy critically affects the quality of life of patients. Maintenance strategies with FP plus bevacizumab have been well established; nonetheless, the real-world outcomes of maintenance therapy with FP and cetuximab are unclear. We investigated the clinical outcomes of patients who underwent maintenance therapy with cetuximab. MethodsWe retrospec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A pooled analysis of anti-angiogenic biologicals, including bevacizumab, ramucirumab, and aflibercept, confirmed the efficacy of these drugs as a second-line treatment of pre-treated BRAF mutant CRC [188]. In addition, a retrospective analysis of the maintenance therapy of FOLFOX-pre-treated BRAF V600E metastatic CRC with bevacizumab plus fluoropyrimidine showed high disease control (74%), and overall survival (25.6 months), warranting further large-scale trials of this promising second-line combination therapy in the future [189]. The global phase 3 RAISE trial with metastatic CRC patients pre-treated with bevacizumab, oxaliplatin, and fluoropyrimidine showed that the anti-VEGFR2 antibody ramucirumab plus FOLFIRI prolonged overall survival and progression-free survival together with an increase of side effects (neutropenia, thrombocytopenia, stomatitis, epistaxis, and hypertension) when compared with FOLFIRI plus placebo, which was accompanied by a substantial benefit of ramucirumab plus FOLFIRI in BRAF mutant patient groups [190].…”
Section: Clinical Trials Of Vegfr Inhibitors In Braf Mutant Cancersmentioning
confidence: 75%
“…A pooled analysis of anti-angiogenic biologicals, including bevacizumab, ramucirumab, and aflibercept, confirmed the efficacy of these drugs as a second-line treatment of pre-treated BRAF mutant CRC [188]. In addition, a retrospective analysis of the maintenance therapy of FOLFOX-pre-treated BRAF V600E metastatic CRC with bevacizumab plus fluoropyrimidine showed high disease control (74%), and overall survival (25.6 months), warranting further large-scale trials of this promising second-line combination therapy in the future [189]. The global phase 3 RAISE trial with metastatic CRC patients pre-treated with bevacizumab, oxaliplatin, and fluoropyrimidine showed that the anti-VEGFR2 antibody ramucirumab plus FOLFIRI prolonged overall survival and progression-free survival together with an increase of side effects (neutropenia, thrombocytopenia, stomatitis, epistaxis, and hypertension) when compared with FOLFIRI plus placebo, which was accompanied by a substantial benefit of ramucirumab plus FOLFIRI in BRAF mutant patient groups [190].…”
Section: Clinical Trials Of Vegfr Inhibitors In Braf Mutant Cancersmentioning
confidence: 75%